Measurement of the W-pair production cross section and W-decay branching fractions in e+e− interactions at √s = 189 GeV - Dova, María Teresa (2000)
The data collected by the L3 experiment at LEP at a centre-of-mass energy of 188.6 GeV are used to measure the W-pair production cross section and the W-boson decay branching fractions. These data correspond to an integrated luminosity of 176.8 pb−1. The total cross section for W-pair production, combining all final states, is measured to be σWW = 16.24 ± 0.37 (stat.) ± 0.22 (syst.) pb. Including our data collected at lower centre-of-mass energies, the hadronic branching fraction of the W-boson is determined to be B(W → qq) = [68.20 ± 0.68 (stat.) ± 0.33 (syst.)]%. The results agree with the Standard Model predictions.